PENGARUH MODEL DISCOVERY LEARNING BERPADU KETERAMPILAN PROSES SAINS TERHADAP HASIL BELAJAR SISWA PADA SUB MATERI BRYOPHYTA - Lubis, Muhajir Syarif; Khairunna, Khairunna; Siregar, Lailatun Nur Kamalia (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Science process skills in the bryophyte sub-material require improvement, one of which is by implementing the discovery learning model. This is because when students learn they only focus on presenting monotonous material. So the psychomotor aspect of the assessment was not carried out. So this research aims to determine the influence and responses of students in the discovery learning model on students' science process skills in the bryophyta sub-material. The design in this research uses an experimental class with the discovery learning model applied and the control class uses conventional learning. The population in this research is all Class X students of SMA Negeri 1 Beringin with a sample of class X-1 as the control class and class By using data collection techniques in the form of pretest and posttest test sheets. Data analysis techniques were carried out using descriptive analysis techniques and inferential analysis techniques. As for the results obtained from the results of science process activities, the average posttest score in the experimental class was 66, while in the control class, it was 46.5. Data analysis using the paired samples test shows that sig < 0.05 with a sig value of 0.00 < 0.05 with a t-count value of 20.784 and t-table 2.01 in discovery learning so that Ho is rejected and Ha is accepted. So it can be concluded that learning using the discovery learning model affects increasing students' science process activities in the bryophyta sub-material.